PENGKAJIAN SUHU RUANG PENYIMPANAN DAN TEKNIK PENGEMASAN TERHADAP KUALITAS BENIH KEDELAI - Indartono, Indartono (Vocational School Diponegoro University, 2011)
Indartono, in this paper explain that soybean seed quality decline if easy packaging and storage techniques are not good. This research aims to study the technique of packing and room temperature on soybean seed quality during the four months of storage. Research conducted at the Laboratory of Postharvest and Alsintan, BPTP Central Java, with a Completely Randomized Design 3 (three) factors and two replications. The first factor varieties (Burangrang, Willis, and Baluran), the second factor technique packaging (vacuum and without vacuum), and the third factor storage temperature (27-29 Â° C and 6 Â° C). During the four storage observed changes in water content, shrinkage and the weight of soybean seed germination. The results showed that the shrinkage weight, water content and temperature of storage space does not give real effect to the power of germination for 4 four months of storage, and storage techniques vacuum (vacuum) to give an average power of germination is higher than without vacuum treatment, but a statistically not significantly different from other treatments by Duncan's test 95% confidence level for all varieties Key words: soybean, room temperature storage, packaging techniques, the germinated